Assessing Household’s Food Security in Patarasi Rural Municipality of Jumla District of Karnali Province, Nepal - Kharel, Suman; Marahatta, Deepak; Limbu, Bhanu (Nepalese Journal of Development and Rural Studies, 2021)
Food security in mountain areas has always been a matter of concern. The purpose of this study is to examine the food security situation and coping strategies in rural households in a mountain area. Following the descriptive research approach, data is collected through implying household survey, semi-structured interview, and observation method. The food security situation is analyzed through four dimensions of food security: food availability, access to food, utilization of food, and stability. The result shows households depend mainly on markets as their main source of household food and households follow inadequate food consumption and the majority of households' food consumption patterns constitute either borderline or poor. Households apply short-term food consumption coping strategies such as lending money from friends or buying food on credit. The study recommends that farming households be supported in terms of both short-term and long-term strategies to improve food production and supply.